2020
DOI: 10.1007/s00330-020-06960-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of new horizontal meniscal tears in individuals at risk for and with mild to moderate osteoarthritis: data from osteoarthritis initiative

Abstract: Objectives To study the natural history of new horizontal meniscal tears and their association with progression of cartilage degeneration in individuals at risk for or with mild to moderate knee osteoarthritis over 4 years. Methods Individuals who developed a new meniscal tear in the right knee over 2 years were selected from the Osteoarthritis Initiative 3T MRI studies. Knee structural changes were analyzed at the time of tear appearance (baseline), and after 4 years using a modified Whole-Organ Magnetic Reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It is currently accepted that the optimal treatment option for small horizontal meniscal tears is arthroscopic repair of the torn meniscus using a suture system, which not only improves the probability of healing of the meniscus but also preserves the internal cushion of the knee joint to the greatest extent possible [ 32 34 ], but because the repair of horizontal tears is more difficult to perform microscopically than longitudinal tears, and because some studies have shown that patients repaired by sutures have a higher complication rate are higher in patients who underwent partial resection [ 35 ], so most physicians prefer partial resection rather than attempting repair when dealing with horizontal meniscal tears [ 36 38 ]. However, when we remove a portion of the meniscus, it inevitably results in a reduction of the contact area within the knee joint, an increase in the peak pressure within the intercompartment, and ultimately causes cartilage wear and tear thereby increasing the risk of osteoarthritis [ 7 , 39 , 40 ]. If a partial meniscectomy with postoperative results close to those of suture repair could be found, it might eliminate clinicians’ hesitation when faced with horizontal meniscal tears.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently accepted that the optimal treatment option for small horizontal meniscal tears is arthroscopic repair of the torn meniscus using a suture system, which not only improves the probability of healing of the meniscus but also preserves the internal cushion of the knee joint to the greatest extent possible [ 32 34 ], but because the repair of horizontal tears is more difficult to perform microscopically than longitudinal tears, and because some studies have shown that patients repaired by sutures have a higher complication rate are higher in patients who underwent partial resection [ 35 ], so most physicians prefer partial resection rather than attempting repair when dealing with horizontal meniscal tears [ 36 38 ]. However, when we remove a portion of the meniscus, it inevitably results in a reduction of the contact area within the knee joint, an increase in the peak pressure within the intercompartment, and ultimately causes cartilage wear and tear thereby increasing the risk of osteoarthritis [ 7 , 39 , 40 ]. If a partial meniscectomy with postoperative results close to those of suture repair could be found, it might eliminate clinicians’ hesitation when faced with horizontal meniscal tears.…”
Section: Discussionmentioning
confidence: 99%
“… 24 HCTs are a significant risk factor for progression to high-grade osteoarthritis within 5 years after partial meniscectomy. 25 , 26 Resection of both leaflets results in decreased contact area and increases contact pressure, which can lead to onset of osteoarthritis development. 27 Recent evidence indicates that repair reduces the relative risk of osteoarthritis almost 3-fold relative to meniscectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that the maximum shear stress of cartilage increases as the resection volume of a meniscectomy increases ( Bedi et al, 2010 ; Zhang et al, 2021 ; Liu et al, 2022 ) and further leads to joint pain, swelling, and even osteoarthritis ( Bedi et al, 2010 ; Beamer et al, 2017 ; Bedrin et al, 2021 ; Ozeki et al, 2022 ). Horizontal tears account for 12%–35% of all tear patterns ( Shanmugaraj et al, 2019 ) and usually occur in the medial menisci (especially the posterior horn of the medial meniscus ( Yim et al, 2013 ; Brown et al, 2016 )) due to joint degeneration ( Lee et al, 2016 ; Jiang et al, 2017 ; Posadzy et al, 2020 ). Due to the limited healing capacity and tissue weakness of meniscal horizontal tears following meniscal repair ( Kurzweil et al, 2014 ; Kurzweil et al, 2018 ; Ogawa et al, 2020 ) or conservative or nonsurgical methods ( Haemer et al, 2007 ; Herrlin et al, 2013 ; Brown et al, 2016 ), the dominant clinical treatment for horizontal meniscal tears is arthroscopic meniscectomy to remove the single-leaf, double-leaf, subtotal body or total body of a meniscus ( Seil et al, 2010 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%